Amtek Auto debacle: financial statement analysis. Issue 2 (30th April 2020) - Pandey, Asheesh
Abstract : Learning outcomes: The learning outcomes are as follows: developing an understanding of financial statement analysis among students; students would be able to calculate various ratios, understand their meaning and interpret them to take a financial decision; and exploring the relationship between financial leverage and risk. Case overview/synopsis: Amtek Auto is a leading auto-components manufacturer established in 1988 which entered into bankruptcy in through the order of Reserve Bank of India in 2017. The company started with a humble beginning and later on the promoter decided to expand exponentially both through organic as well as inorganic growth in past 15 years. To grow a company kept on taking debt which made it riskier and deteriorated its financial position over a period. The case covers a 10-year timeline from 2008 to 2017. It gives an opportunity to analyze its financial statements to understand how its decisions shaped its performance Complexity academic level: The case aims for students to take a comprehensive view of the financial statement analysis of Amtek Auto including the following: vertical and horizontal analysis; comprehensive ratio analysis including liquidity, profitability, leverage and turnover ratios with special emphasis on debt as a double-edged sword; analysis of Armtek Auto's financial performance over a period of 10 years. Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS 1: Accounting and Finance.